2001
DOI: 10.1111/j.1574-6941.2001.tb00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracing toluene-assimilating sulfate-reducing bacteria using 13C-incorporation in fatty acids and whole-cell hybridization

Abstract: Polar lipid-derived fatty acids (PLFA) commonly found in sulfate-reducing bacteria were detected in high abundance in the sediment harvested from a monitoring well of a petroleum-hydrocarbon (PHC)-contaminated aquifer. Aquifer microcosms were incubated under sulfate-reducing conditions with [methyl-14 C]toluene to determine the 14 C-mass balances and with [methyl-13 C]toluene to follow the flow of carbon from toluene into biomarker fatty acids. An aliquot was used to establish an aquifer-derived toluene-degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Syntrophobacteraceae were identified in a toluene-degrading sulfate-reducing bacterial consortium, but in that study, the Desulfobulbaceae were identified as key organisms of toluene degradation within the consortium (43). In another study, polar lipid-derived fatty acid SIP in combination with whole-cell hybridization linked toluene degradation to the Desulfobacter-like populations, while Syntrophobacteraceae were present in the microbiota but not responsible for toluene biodegradation (45). The Syntrophobacteraceae were also observed in a benzene-degrading in situ microcosm but were not linked to benzene biodegradation (23).…”
Section: Resultsmentioning
confidence: 90%
“…Syntrophobacteraceae were identified in a toluene-degrading sulfate-reducing bacterial consortium, but in that study, the Desulfobulbaceae were identified as key organisms of toluene degradation within the consortium (43). In another study, polar lipid-derived fatty acid SIP in combination with whole-cell hybridization linked toluene degradation to the Desulfobacter-like populations, while Syntrophobacteraceae were present in the microbiota but not responsible for toluene biodegradation (45). The Syntrophobacteraceae were also observed in a benzene-degrading in situ microcosm but were not linked to benzene biodegradation (23).…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, following the reasoning of Parkes et al [48], these carbon sources may not necessarily be present or used by the SRB in situ in this sediment. Instead, SRB may be directly involved in degradation of PHC constituents [29]. We are aware of the problem that the dominant types of SRB in microcosms may change with increasing incubation time, especially on substrates that are incompletely oxidized [48].…”
Section: Discussionmentioning
confidence: 99%
“…However, we must be aware that yet undiscovered SRB species and genera may inhabit anaerobic environments [30,31]. Only a few authors have characterized SRB communities in freshwater [32,33] and direct information on SRB in PHC-contaminated freshwater environments is even more limited [29].…”
Section: Introductionmentioning
confidence: 99%
“…A 13 C-labeled acetate pulse was administered to sediments, with the resulting 13 C-enriched polar-lipid-derived fatty acid (PLFA) signature profiles subsequently being preferentially analyzed. Other studies utilizing the same approach have followed suit (9,24).…”
mentioning
confidence: 99%